2017
DOI: 10.3904/kjim.2016.054
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma prognostic index at diagnosis might be a prognostic marker in patients newly diagnosed with multiple myeloma

Abstract: Background/AimsThe aims of this study were to identify the value of inflammatory markers as pretreatment prognostic factors for patients with multiple myeloma (MM) and to estimate the value of a prognostic index including these markers at diagnosis.MethodsA total of 273 newly diagnosed MM patients undergoing active treatment were analyzed in this study. The prognostic values for survival of the pretreatment inflammatory markers were investigated. A myeloma prognostic index (MPI) was derived using prognostic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Treatment with lenalidomide provides an alternative choice for elderly patients and those unable to tolerate chemotherapy ( 16 , 17 ). In addition, prognostic factors, including peripheral lymphocytes and CRP, have been reported and were demonstrated to have a varying prognostic significance in traditional chemotherapy and novel drug protocols ( 4 , 5 , 18 , 19 ). This highlights the importance of discovering and identifying prognostic markers in MM for novel treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with lenalidomide provides an alternative choice for elderly patients and those unable to tolerate chemotherapy ( 16 , 17 ). In addition, prognostic factors, including peripheral lymphocytes and CRP, have been reported and were demonstrated to have a varying prognostic significance in traditional chemotherapy and novel drug protocols ( 4 , 5 , 18 , 19 ). This highlights the importance of discovering and identifying prognostic markers in MM for novel treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of affected individuals is 72 years for men (75% >70 years) and 71 years for women (79% >70 years) ( 3 ). In addition to genetic markers, there are further prognostic factors, including lymphocyte counts and C-reactive protein (CRP) expression level, which have been evaluated in recent years ( 4 , 5 ). Immunophenotyping, including the analysis of CD19, CD45, CD56 and CD117, is of great value to the prognosis and diagnosis of MM according to recent reports ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies have examined its impact on MM as well. High NLRs in patients with MM are associated with negative prognosis in these studies . The specific mechanism involved in the interaction between increased NLR and poor prognosis of multiple myeloma patients is incompletely understood.…”
Section: Discussionmentioning
confidence: 84%
“…Lihui and Shi calculated the cutoff value of NLR as 4. In other studies, NLR cutoff values were given as 2, 2.25, and it was obtained as 2.78 . The cutoff values for NLR were calculated as 3.19 on day −5 prior ASCT and 1.46 on day +100 after ASCT in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Kim et al [5] have very recently evaluated the prognostic value of baseline NLR in 273 newly diagnosed MM patients. Multivariate analysis revealed that poor performance status (≥2), a high percentage of plasma cells in the bone marrow, a high cytogenetic risk, a high NLR, a low platelet count, elevated C-reactive protein, the use of novel agents (bortezomib, thalidomide, and lenalidomide), and stem cell transplantation were independent and significant prognosticators of OS.…”
mentioning
confidence: 99%